2019
DOI: 10.1016/j.parepi.2018.e00080
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Toxoplasma gondii infections in swine of non-tecnified rearing farms of the northeastern region of the state of São Paulo, Brazil and associated risk factors

Abstract: Toxoplasmosis is a zoonosis present worldwide. Its protozoal aethiological agent, Toxoplasma gondii, has the ability to infect several homeothermic animals and mainly human beings. The consumption of raw or undercooked meat products containing T. gondii cysts, consumption of vegetables without washing and using non-treated water are risk factors associated to the occurrence of human toxoplasmosis. Furthermore, raw or undercooked pork is an important infection source of T. gondii to humans. Due to the importanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…To the best of our knowledge, this was the first study to report on the circulation of T. gondii in pigs in this area. These data are of public health relevance, because pigs act as reservoirs for this protozoan and consumption of pig meat under these conditions represents a risk to human health, as already shown in previous studies (Dubey, 2009;Vergara et al, 2018;Miura et al, 2019;Oliveira et al, 2018;Santos et al, 2019). In addition, investigations on occurrences of T. gondii in pigs form an important step within surveillance and control of foodborne toxoplasmosis.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…To the best of our knowledge, this was the first study to report on the circulation of T. gondii in pigs in this area. These data are of public health relevance, because pigs act as reservoirs for this protozoan and consumption of pig meat under these conditions represents a risk to human health, as already shown in previous studies (Dubey, 2009;Vergara et al, 2018;Miura et al, 2019;Oliveira et al, 2018;Santos et al, 2019). In addition, investigations on occurrences of T. gondii in pigs form an important step within surveillance and control of foodborne toxoplasmosis.…”
Section: Discussionsupporting
confidence: 56%
“…The estimated global prevalence of infection by this important foodborne pathogen is 30% (Haq et al, 2016). In Brazil, serological studies on pigs have shown varying prevalences, with widespread distribution throughout the country, ranging from 1.32% to 90.4% (Cavalcante et al, 2006;Azevedo et al, 2010;Oliveira et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Argentina is known as a meat consumer country, specially from bovine animals (Gallup, 2005). To notice, the consumption of porcine and ovine meat has increased in recent times, which are known as possible sources of T. gondii infection (Oliveira et al., 2018) (Dubey, 2009). Therefore, we investigated different meat types as potential risk factor.…”
Section: Resultsmentioning
confidence: 99%
“…Sows, pigs from farms with low hygiene standards, and pigs from organic farms, were more likely to have high antibody titers (≥ 1600) than those in other groups; this may indicate the presence of an acute infection [ 74 , 75 ]. Animals with high antibody titers are more likely to present living parasites (tachyzoites) in the blood on analysis, thus indicating the presence of parasitemia.…”
Section: Discussionmentioning
confidence: 99%
“…Its duration in pigs has not been determined [ 42 ]. Low titers may indicate chronic infection [ 75 ].…”
Section: Discussionmentioning
confidence: 99%